2012
DOI: 10.5433/1679-0359.2012v33n2p471
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade combinatória e efeito recíproco em características agronômicas do feijão

Abstract: ResumoO objetivo deste trabalho foi avaliar a capacidade geral de combinação dos genitores envolvidos nos cruzamentos e a capacidade específica de combinação dos híbridos, bem como o efeito recíproco em relação as características agronômicas em feijoeiro. Inicialmente foram realizados os cruzamentos dialélicos, intercruzando os seis genitores: Xan 159, Pérola, BAF 63, IPR Uirapuru, BRS Supremo, BRS Valente, gerando trinta e seis combinações. As sementes F 1 juntamente com os genitores foram levadas a campo em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
3
10
0
2
Order By: Relevance
“…The obtained emergence results also agree with what was reported by Baldissera et al (2012), who, in a study on combinatorial ability and reciprocal effect on the agronomic characteristics of beans, concluded that reciprocal effect evaluations confirm the existence of differences when a plant is used as a male or female genitor, since there is the presence of cytoplasmic effect and nuclear genes of the female genitor in the evaluated characters. According to Gomes et al (2000), the correct choice of maternal and paternal parents is important for the formation of hybrid maize seeds with high germination power.…”
Section: Resultssupporting
confidence: 90%
“…The obtained emergence results also agree with what was reported by Baldissera et al (2012), who, in a study on combinatorial ability and reciprocal effect on the agronomic characteristics of beans, concluded that reciprocal effect evaluations confirm the existence of differences when a plant is used as a male or female genitor, since there is the presence of cytoplasmic effect and nuclear genes of the female genitor in the evaluated characters. According to Gomes et al (2000), the correct choice of maternal and paternal parents is important for the formation of hybrid maize seeds with high germination power.…”
Section: Resultssupporting
confidence: 90%
“…We observed a predominance of estimates of additive variance related to dominance for the 3 populations in the 2 seasons (Table 4). Baldissera et al (2012) and Silva et al (2013b) also observed a predominance of additive effects in HD genetic control. Heritability estimates of family means ranged from 55 to 76% for the 3 populations over the 2 seasons (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, according to Ramalho et al (2000), one should take into consideration the parental behavior, which can be used either as female (pollen recipient), or as male (pollen donor). Baldissera et al (2012) evaluated the crosses from six bean parents without stress induction and founding Table 1. Summary of analysis of variance for combining ability referring to yield (GY), one thousand grain weight (SW), number of pods per plant (NPP), number of seeds per pod (NSP), plant height (PH), total leaf area (LA), dry weight of shoots (DMS), stomatal conductance (SC), leaf water potential (Ψw) measured at 13 pm.…”
Section: Resultsmentioning
confidence: 99%